Remoção de metais pesados utilizando carvão ativado para obtenção de água potável - Bazana, Simone de Lima (2014)
Due to uncontrolled population growth and consequently the increase in industrial and agro-industrial sector, the concern about the quality of water is growing. These factors are generally responsible for discharges sometimes irregular in aquatic environment, whether in rural or urban areas. The water treatment plants (WTP) aimed at improving the process on this issue, but due to irregularities such as illegal disposal of industrial effluents, pipelines without proper maintenance domestic water storage tanks poorly preserved and poorly designed wells contribute significantly to a high concentration of contaminants in the drinking water, and sometimes surpassing the parameters for drinking water established by law. Faced with this problem the development of new technologies for the treatment and post-treatment of water for human consumption is a growing need. This study aimed to develop commercial gravitational filtration modules with activated carbon impregnated with metal ions (silver and combination of silver ions and copper) on the surface of activated vegetable carbon of babassu and coconout. The metal ions were impregnated using the method of impregnation by excess solvent. The concentration of impregnation used were those obtained better results in the efficiency of removal of bacteria, protozoa and virus. The influence of metal ions on activated carbon was determined by textural characterization: specific surface area (BET), micropore area (method t), volume and diameter of microporos (method HK) and volume and diameter of mesopore (method BJH). The structural characterization was performed by analysis of X-rays diffraction (DRX) and the percentage removal was analyzed by atomic absorption flame atomizer. The impregnation of metal ions on activated carbon modified its features, showing changes in the format and size of the pores. The activated carbon filters impregnated with metal ions were evaluated for effectiveness in reducing physical and chemical parameters (color, turbidity, pH, free chlorine) and removal efficiency of heavy metals such as zinc, iron and lead in synthetic water (water artificially contaminated with lead nitrate, iron sulphate and zinc chloride). The analyzed physico-chemical parameters (color, turbidity, pH, free chlorine) remained in compliance with the standard of acceptance for human consumption, according to the Ordinance 2914/2011 and ABNT NBR 15176. It was concluded that the used adsorbent influences in the removal efficiency of heavy metals. Removal of the lead contaminant of the water for human consumption remained in accordance with the accepted standard for all analyzed filtration modules. The filter module babassu proved efficient in removing zinc. For the iron contaminant the efficient filtration modules were: coal of babassu and coal of coconout impregnated with silver and copper ions